Learner-Centered Teaching: A Case Study of its Implementation in Physics and Chemistry Classes in Moroccan High Schools - El Hammoumi, Mohamed Merouane; Bakkali, Said; El Youssfi, Safaa (European Scientific Journal, ESJ, 2020)
Following the international call of the learner-centered approach, the Moroccan educational system has undergone a paradigm shift in teaching methods. Physics and chemistry textbooks used in Moroccan high schools highly valorise learning strategies development, self-directed learning, and discovery learning, which promote the learner’s autonomy. This study provides an overview of the learner-centeredness principles, and it is based on data collection which is accomplished using a questionnaire administered to 35 physics and chemistry high school teachers. It focuses on analysing the teachers’ attitudes towardsthis approach. The study shows that majority of the teachers are motivated towards implementing the learner-centered approach, but very few of them rely on both teacher and student-centered teaching simultaneously to cater for students’ learning needs. This paper recommends the use of active learning to cater for a successful educational system.